Developing Local Based Content Supplementary Reading Material for Senior High School - Sastika Seli; Dewi Syafitri; Indriani Indriani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The aim of this research was to find out validity, practicality, and effectiveness of a developed book entitled Developing Local Based Content Supplementary Reading Material for Senior High School in Lubuklinggau. In conducting the research, Research and Development written by Branch (2009) consisting of analysis, design, development, implementation and evaluation (ADDIE) was used as steps in developing the product meanwhile Formative Evaluation written by Tessmer (1993) was used to evaluate the data. To determine the validity of the book, three experts were included to review the product namely content expert, instructional design expert, and layout quality expert. To determine the practicality and effectiveness of the product, three students were involved in one-to-one trial, sixt students were involved in small group trial, and ten students were involved in a field test. The practicality and effectiveness values were obtained from tenth grade students in Senior High School number 1 Lubuklinggau in academic year 2021-2022 which were taken as subjects of the research. To collect the data, questionnaire, interviews, and a test were used. The collected data were analyzed qualitatively for the interview and quantitatively by using average score for the questionnaire and the test. After all data had been analyzed, it could be concluded that the product as a book was categorized highly valid with average score 3.76, categorized very highly practical with average score 4.67 at one-to-one trial and 4.32 at small group trial, and categorized very highly effective with average score 90.